Blood and chocolate - Klause, Annette Curtis (New York : Bantam Doubleday Dell Books for Young Readers, 1999)
Having fallen for a human boy, a beautiful teenage werewolf must battle both her packmates and the fear of the townspeople to decide where she belongs and with whom.
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
6.2
Young Adult
Keywords: Horror stories; Werewolves -- Fiction; Horror fiction; Werewolves -- Fiction